Best Practice in Public Expenditure Reviews Togo : A Participatory Approach - World Bank (Washington, DC, 2012)
The Public Expenditure Review (PER) carried out in Togo in November 1995-November 1996 had two principal objectives: to assist the government in identifying priorities to increase the efficiency and equity of public spending; and to internalize the expenditure review exercise. The PER process included several features designed to strengthen government capacity and ownership: 1) a one-day in-country workshop on expenditure issues which was attended by over 70 government officials from various ministries and government agencies; 2) a two-week workshop held in Washington, DC, attended by key Directors from central and sectoral ministries involved in public expenditure management; and 3) follow-up in-country meeting within the Togolese administration the recommendations that emerged from the Washington workshop.